SARS-CoV-2 evolution and within-host variation in nonhuman animals - Bashor, Laura, author; VandeWoude, Sue, advisor; Stenglein, Mark, committee member; Bosco-Lauth, Angela, committee member; Sloan, Dan, committee member; Gagne, Roderick B., committee member (Colorado State University. Libraries, 2024)
The COVID-19 pandemic originated following spillover of SARS-CoV-2 from non-human animals into humans. Despite concentrated efforts before and after the pandemic, current research is constrained by the impracticality of witnessing initial host shift events and transmission dynamics that shape infectious disease emergence. SARS-CoV-2 transmission from humans to a range of domestic and wild species has been well documented; furthermore, spillback into humans from white-tailed deer, mink, hamsters, domestic cats, and lions has also been reported. SARS-CoV-2, like other RNA viruses, has the ability to adapt rapidly following host shifts. These cross-species transmission events can accelerate novel variant emergence through selection for genetic variation that improves virus fitness in a novel host environment. To evaluate the possibility that cross-species transmission accelerates SARS-CoV-2 evolution and variant emergence, we employed next-generation sequencing of viral genomes recovered from experimentally and naturally infected animals to characterize within-host virus populations. We demonstrated the use of experimental exposure studies as a controlled system to test hypotheses surrounding SARS-CoV-2 adaptation in cats (Felis catus), dogs (Canis lupus familiaris), hamsters (Mesocricetus auratus), ferrets (Mustela putorius furo), deer mice (Peromyscus maniculatus), bushy-tailed woodrats (Neotoma cinerea), Brazilian free-tailed bats (Tadarida brasiliensis), striped skunks (Mephitis mephitis), red foxes (Vulpes vulpes) and mule deer (Odocoileus hemionus). We also evaluated publicly available sequencing data from infected felids, and investigated within-host dynamics in natural infections of Amur tigers (Panthera tigris altaica), African lions (Panthera leo), and spotted hyenas (Crocuta crocuta) in a zoo environment. Our initial work investigated SARS-CoV-2 evolution across three passages in Vero cells and experimentally infected cats (n = 6), dogs (n = 3), hamsters (n = 3), and a ferret (n = 1). We observed the rapid selection and fixation of five SARS-CoV-2 mutations in Vero cells, followed by their reversion in dogs, cats and hamsters 1-3 days post-infection. We noted 14 emergent variants across the SARS-CoV-2 genome, including increased variation in the SARS-CoV-2 spike protein. Emergent variants included mutations not detected in the original virus stocks used for inoculation, and several defining mutations of variant lineages of concern in humans. Finally, we noted increased signs of adaptation in dogs, which did not shed infectious virus, including six nonsynonymous mutations in the SARS-CoV-2 open-reading frames (ORFs) encoding proteins for virus replication. In particular, this work underscored the potential for accelerated viral evolution in cell culture systems used commonly in virological research. This work has been published and represents Chapter 2 of this dissertation. Our next study built upon this work by investigating SARS-CoV-2 evolution in three experimental cohorts of domestic cats (n=23) infected through direct inoculation and cat-to-cat contact transmission. We observed high numbers of within-host variants in SARS-CoV-2 genomes recovered from cats compared to what is documented in humans, over half of which were nonsynonymous changes. The number of variants detected was positively correlated with the experimental dose of virus inoculum, and fewer variants were observed in contact cats. Similar to the previous study, mutations occurring at the same positions as defining VOC mutations, and signatures of positive selection in the viral spike (S) gene were observed. Our concurrent analysis of publicly available SARS-CoV-2 sequences showed no evidence for independent evolutionary trajectories associated with natural infections of domestic cats or other felids, and confirmed susceptibility of felids to the breadth of variants circulating in human populations. This work has also been published and represents Chapter 3 of this dissertation. We subsequently investigated SARS-CoV-2 evolution in longitudinal samples collected from Amur tigers (n=2), African lions (n=11), and spotted hyenas (n=4) infected during an outbreak at the Denver Zoo. Longitudinal nasal swabs were collected from infected individuals over an approximately three-month sampling period. We determined that the outbreak was caused by a single introduction of the Delta sublineage AY.20, which was a rare variant circulating in human populations at the time. We inferred a transmission chain from tigers to lions to hyenas, which was consistent with the appearance of clinical signs in infected animals. We observed expansion and diversification of within-host virus populations, and signatures of both purifying and positive selection. The strongest signs of positive selection were evident in the viral nucleocapsid (N) gene, and in viruses recovered from hyenas. Four candidate species-specific adaptive mutations, two of which are in the N gene, were identified in lions and hyenas (N A254V) and hyenas alone (ORF1ab E1724D, S T274I, and N P326). This work is presented in Chapter 4 of this dissertation. In Chapter 5, we evaluated a large dataset of peridomestic wildlife species experimentally infected with two SARS-CoV-2 variants, WA01 and Delta. Study species included deer mice (n=3), bushy-tailed woodrats (n=3), Brazilian free-tailed bats (n=4), striped skunks (n=5), red foxes (n=9), and mule deer (n=6). Distinct dynamics were observed in within-host virus populations recovered from WA01- and Delta- infected animals. This included increased within-host variation, relative effective population size, and genomic signatures of positive selection in WA01 animals. In contrast to our first study in domestic dogs, Brazilian free-tailed bats, which also did not shed infectious virus, did not show increased signs of adaptation. We also observed a potential host barrier to infection in skunks and one fox, followed by the emergence of potential de novo mutations. Six novel mutations were also detected in contact-exposed mule deer. Our findings suggest that mule deer populations, similar to what has been documented in closely related white-tailed deer, should be investigated for accelerated SARS-CoV-2 evolution. Collectively, our work reveals the unique dynamics of SARS-CoV-2 evolution and transmission in both naturally- and experimentally- infected felids. We observed rapid viral adaptation both in vitro and in vivo, highlighting advantages and limitations of experimental animal infections for studies of viral evolution. In each study, we used publicly available data to contextualize our experimental data and identify broader patterns. Furthermore, we identified specific SARS-CoV-2 mutations and genomic regions under selective pressures across a range of animal species, setting the groundwork for future mechanistic studies. Our findings underscore the importance of a One Health approach to understanding SARS-CoV-2 evolution, and the need for surveillance in animal populations.
Zip file contains supplementary tables.
Keywords: nonhuman animals; virus evolution; felids; within-host variation; SARS-CoV-2